Teaching listening comprehension - Ur, Penny (Cambridge : New York : Cambridge University Press, 1984)
This book is about developing listening comprehension skills in the language classroom. In Part I, some essential background issues are dealt with. The author defines the characteristics of real-life listening, analyses the problems encountered by language learners, and discusses the considerations involved in planning successful classroom listening practice. Part II contains a wide variety of exercise types. The activities range in level from elementary to advanced and illustrate techniques appropriate for both adults and children. The exercises can be used as they stand or they can serve as models for teachers who wish to design their own materials. -- Back cover.
Includes bibliography and index.
Keywords: Listening -- Study and teaching; Attention; Comprehension; Listening comprehension